The Escherichia coli mraY gene encoding UDP-N-acetylmuramoyl-pentapeptide: undecaprenyl-phosphate phospho-N-acetylmuramoyl-pentapeptide transferase. - Ikeda, M (1991)
Amplification of the mraY gene, previously called open reading frame Y (ORF-Y, 1,080 bp), at 2 min in the chromosome map of Escherichia coli enhanced the activity of UDP-N-acetylmuramoyl-pentapeptide: undecaprenyl-phosphate phospho-N-acetylmuramoyl-pentapeptide transferase (EC 2.7.8.13). This enzyme catalyzes the formation of undecaprenyl-pyrophosphoryl-N-acetylmuramoyl-pentapeptide from UDP-N-acetylmuramoyl-pentapeptide and undecaprenyl-phosphate, the first step in the lipid cycle reactions in biosynthesis of bacterial cell wall peptidoglycans. The enhanced enzyme activity was sensitive to tunicamycin, and the amino tunicamycin-sensitive N-acetylglucosamine-1-phosphate transferase of Saccharomyces cerevisiae. Very probably mraY is the structural gene for the above enzyme.